2006
DOI: 10.1093/ajcn/84.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte propionyl-CoA carboxylase and its activation by biotin are sensitive indicators of marginal biotin deficiency in humans

Abstract: PCC activity is the most sensitive indicator of biotin status tested to date. In future pregnancy studies, the use of lymphocyte PCC activity data should prove valuable in the assessment of biotin status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Analyses were performed on urine samples obtained from participants in a study previously reported (4)(5)(6). The Institutional Review Board for the University of Arkansas for Medical Sciences approved this study.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Analyses were performed on urine samples obtained from participants in a study previously reported (4)(5)(6). The Institutional Review Board for the University of Arkansas for Medical Sciences approved this study.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Urinary excretion of 3HIA and 3HIA-carnitine was also shown to significantly increase in response to an oral challenge of leucine, an amino acid whose degradation requires MCC (Mock et al, 2002a;Mock et al, 2011). A decrease in PCC activity in lymphocytes and, more recently, an increase in the ratios of acylcarnitines in urine, arising from acyl-CoA substrates and their products, which reflect disturbances in biotin-dependent carboxylase activities, were also observed in response to induced biotin insufficiency (Stratton et al, 2006;Bogusiewicz et al, 2012).…”
Section: Biomarkersmentioning
confidence: 99%
“…While the abundance of biotinylated proteins depends on biotin supply in adults (Chew et al 2008;Stratton et al 2006) and human cell cultures (Camporeale et al 2007a;Chew et al 2008;Gralla et al 2008;Pestinger et al 2011), human biotin requirements are still unknown (National 1998). Depletion of histone biotinylation causes deregulation of genes (Camporeale et al 2007b;Gralla et al 2008;Pestinger et al 2011).…”
Section: Biotinylation Of Histonesmentioning
confidence: 99%